A cryogenic detection system at 28.9 MHZ for the non-destructive observation of a single proton at low particle energy - Ulmer, Stefan; Blaum, Klaus; Kracke, H.; Mooser, A.; Quint, Wolfgang; Rodegheri, Crícia de Carvalho; Walz, J. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2013)
A highly sensitive detection system for the non-destructive measurement of the cyclotron frequency of a single proton stored in a cryogenic Penning trap is described. The detector consists of a low noise GaAs field effect transistor amplifier combined with a copper helical resonator with high quality factor. The resonance frequency can be tuned with a GaAs-varactor diode. Connected to the Penning trap a quality factor of 1250 at 28.9MHz is achieved. With this detection system the signal of a single proton at a cyclotron mode-energy of only 10meV was resolved.
Available online 20 December 2012
Gesehen am 17.02.2022